2001
DOI: 10.1080/03079450120066368
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a coronavirus from turkey poults in Europe genetically related to infectious bronchitis virus of chickens

Abstract: Intestinal contents of 13-day-old turkey poults in Great Britain were analysed as the birds showed stunting, unevenness and lameness, with 4% mortality. At post mortem examination, the main gross features were fluid caecal and intestinal contents. Histological examination of tissues was largely unremarkable, apart from some sections that showed crypt dilation and flattened epithelia. Negative contrast electron microscopy of caecal contents revealed virus particles, which in size and morphology had the appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 44 publications
2
91
1
8
Order By: Relevance
“…The gene order of IBV is 59-replicase-S-3-M-5-N-39 UTR. We have established in this study that both pf/CH/LKQ3/03 and tl/CH/LDT3/03 have the same S-3-M-5-N gene order (the replicase and 39 UTR sequences were not determined in this study), as is the case for coronaviruses from turkeys (Breslin et al, 1999a, b;Cavanagh et al, 2001) and pheasant (Cavanagh et al, 2002). Consequently, the coronaviruses from domestic peafowl and teal are related closely to avian coronaviruses that are in group 3, and are distinct from mammalian coronaviruses that are in groups 1 and 2 (Lai & Cavanagh, 1997 tl/CH/LDT3/03, in contrast to pf/CH/LKQ3/03, was more similar to field IBV isolates from China than to the vaccine strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene order of IBV is 59-replicase-S-3-M-5-N-39 UTR. We have established in this study that both pf/CH/LKQ3/03 and tl/CH/LDT3/03 have the same S-3-M-5-N gene order (the replicase and 39 UTR sequences were not determined in this study), as is the case for coronaviruses from turkeys (Breslin et al, 1999a, b;Cavanagh et al, 2001) and pheasant (Cavanagh et al, 2002). Consequently, the coronaviruses from domestic peafowl and teal are related closely to avian coronaviruses that are in group 3, and are distinct from mammalian coronaviruses that are in groups 1 and 2 (Lai & Cavanagh, 1997 tl/CH/LDT3/03, in contrast to pf/CH/LKQ3/03, was more similar to field IBV isolates from China than to the vaccine strains.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of these clones revealed that both newly isolated avian coronaviruses had the S-3-M-5-N gene order that is typical of group 3 coronaviruses from chicken (IBV) (Boursnell et al, 1987), turkey (Breslin et al, 1999a;Cavanagh et al, 2001;Lin et al, 2002) and pheasant (Cavanagh et al, 2002).…”
Section: Partial Genome Organization Of the Two Coronavirus Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, differences between the nucleotide sequence of the S3 (Kapczynski et al, 2002) and S2 genes (Sellers et al, 2004) from turkeys, when compared with chicken and duck isolates were demonstrating, suggesting their classification in a different subgroup, the Orthoreovirus genus. Breslin et al (1999) and Cavanagh et al (2001) showed close genetic relationship between TCoV and infectious bronchitis virus, and Guy (2000) suggested a classification in the group 3 coronavirus, as confirmed by Gomaa et al (2008) by the analysis of the complete genome of TCoV . Imada et al (2000) sequenced the avian nephritis virus, which was classified as a member of the family Astroviridae, and this the first avian astrovirus which genome was completely sequenced, showing close similarity to the turkey astrovirus.…”
Section: Nucleic Acid Technologymentioning
confidence: 97%
“…Recent data from the USA and the UK indicate that coronaviruses associated with acute enteritis in turkey poults are genetically related to infectious bronchitis virus (IBV) of chicken and not to BCoV (Breslin et al, 1999;Cavanagh et al, 2001;Ismail et al, 2002;Loa et al, 2000), contrary to Canadian and US isolates characterized in the early 1990s (Dea et al, 1990 ;Verbeek & Tijssen, 1991) and even until very recently (Lin et al, 2002). In addition to the four structural proteins of all coronaviruses -N (nucleophosphoprotein, 50-60 kDa), M (matrix glycoprotein, 20-26 kDa), E (small membrane protein, 9n5 kDa) and S (peplomeric glycoprotein, 180-200 kDa) -coronaviruses of the second subgroup (haemagglutinating coronaviruses) also possess a 140 kDa envelope-associated glycoprotein, the haemagglutinin-esterase (HE), which is made of two 65 kDa subunits linked together by disulfide bonds (Dea & Tijssen, 1989 ;Hogue & Brian, 1986 ;King et al, 1985).…”
mentioning
confidence: 99%